2005
DOI: 10.1007/s00428-005-1236-0
|View full text |Cite
|
Sign up to set email alerts
|

Type and prevalence of BRAF mutations are closely associated with papillary thyroid carcinoma histotype and patients’ age but not with tumour aggressiveness

Abstract: A high prevalence of the BRAF(V600E) somatic mutation was recently reported in several series of papillary thyroid carcinomas (PTC). This mutation appears to be particularly prevalent in PTC with a predominantly papillary architecture. Another BRAF mutation (K601E) was detected in a follicular adenoma and in some cases of the follicular variant of PTC. The few studies on record provided controversial data on the relationship between the occurrence of BRAF mutations and clinicopathologic parameters such as gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
240
4
11

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(285 citation statements)
references
References 21 publications
30
240
4
11
Order By: Relevance
“…The V600E BRAF mutation has been shown in approximately 43% of PTC (Lupi et al, 2007), ranging from 12% in PTC-FV to 77% in PTC-TCV (Xing, 2005). Interestingly, a distinct BRAF mutation (K601E) had been exclusively found in PTC-FV (Trovisco et al, , 2005 miRNA profiling in follicular thyroid tumours S-Y Sheu et al and in FA (Lima et al, 2004). The genetic and morphologic overlap of PTC-FV is also supported by the results of Castro et al (2006) who found similar frequencies of activating point mutations of the RAS genes and PAX8-PPARg rearrangement in PTC-FV, FA and FTC; both genetic alterations are absent (PAX8-PPARg; Kroll et al, 2000;Nikiforova et al, 2002) or exceedingly rarely (RAS; Vasko et al, 2003) found in 'non follicular variant' of PTC.…”
Section: Discussionmentioning
confidence: 99%
“…The V600E BRAF mutation has been shown in approximately 43% of PTC (Lupi et al, 2007), ranging from 12% in PTC-FV to 77% in PTC-TCV (Xing, 2005). Interestingly, a distinct BRAF mutation (K601E) had been exclusively found in PTC-FV (Trovisco et al, , 2005 miRNA profiling in follicular thyroid tumours S-Y Sheu et al and in FA (Lima et al, 2004). The genetic and morphologic overlap of PTC-FV is also supported by the results of Castro et al (2006) who found similar frequencies of activating point mutations of the RAS genes and PAX8-PPARg rearrangement in PTC-FV, FA and FTC; both genetic alterations are absent (PAX8-PPARg; Kroll et al, 2000;Nikiforova et al, 2002) or exceedingly rarely (RAS; Vasko et al, 2003) found in 'non follicular variant' of PTC.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the BRAF V600E mutation varies according to the histological subtype; the mutation is frequent in the tall cell variant and classic PTC, but absent in the cribriform-morular variant (Trovisco et al 2005). The clinical importance of the BRAF mutation derives from its role as a prognostic factor.…”
Section: Introductionmentioning
confidence: 99%
“…The main mutation of BRAF, identified exclusively in PTC, affects nucleotide 1799 in exon 15 and results in thymine-toadenine transversion, which translates into valine-to-glutamate substitution at residue 600 (p.V600E). 17 The adjacent p.K601E mutation has rarely been identified, 18 and no mutation in exon 11 has been described in thyroid cancers. BRAF mutations are associated with poor clinical prognosis due to extrathyroid invasion and higher risk of relapse and metastasis.…”
mentioning
confidence: 99%